Effect of letrozole and dexamethasone combination therapy compared to letrozole alone for ovulation induction in infertile women with polycystic ovary syndrome: a randomized controlled trial - Ariful Islam, M.; Alam, Humaira; Hossain, Fawzia; Khatun, Sumyara; Nessa, Amitun; Sultana, Rebeka; Al Tarique, Mostafa M.; Banu, Jesmine (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Polycystic ovary syndrome (PCOS), a common cause of anovulatory infertility, affects 5–10% of reproductive-age women. Hyperandrogenemia disrupts follicular development. Dexamethasone may enhance folliculogenesis. This study compared letrozole plus dexamethasone versus letrozole alone for ovulation induction in infertile PCOS women. Methods: This randomized controlled trial was conducted at the Department of Reproductive Endocrinology and Infertility, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh, from September 2023 to August 2024. 72 infertile PCOS women (18-35 years) were allocated into 2 groups. Group A (36 patients) received letrozole 7.5 mg/day for 5 days with dexamethasone 0.5 mg twice daily for 10 days from cycle day 2. Group B (36 patients) received letrozole 7.5 mg/day for 5 days from cycle day 2 for 3 cycles. TVS folliculometry assessed ovarian response on day 12-14. HCG injection was given for mature follicles. Ovulation was confirmed by mid-luteal progesterone and pregnancy by serum B-HCG. Results: Group A showed more mature follicles than group B, notably in the 3rd cycle (76.7% vs 51.6%, p<0.05). Endometrial thickness was greater in Group A in both 2nd (7.7±1.4 vs 6.6±0.9 mm, p<0.05) and 3rd cycles (7.9±1.4 vs 6.7±1.0 mm, p<0.05). Ovulation rates were higher in Group A, reaching significance in the 3rd cycle (76.7% vs 51.6%, p<0.05). Cumulative pregnancy rates favored Group A (30.6% vs 19.4%), though not significantly. Conclusions: Letrozole plus dexamethasone is more effective than letrozole alone in enhancing follicular development, endometrial thickness, ovulation, and pregnancy outcomes in women with PCOS.